До питання про принципи правового регулювання державної території в Україні - Долматов, Іван Володимирович; Долматов, Иван Владимирович; Dolmatov, I. (My University, 2010)
Basic principles of adjusting of state territory are characterized in the article, developed in scientiﬁ c literature. On the basis of study and analysis of constitutional legislation of Ukraine the extended list of these principles is given.
Долматов І. В. До питання про принципи правового регулювання державної території в Україні / І. В. Долматов // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 196-202.
Keywords: правове регулювання державної території в Україні; конституційне законодавство України; правовое регулирование государственной территории в Украине; конституционное законодательство Украины; legal regulation of the national territory in Ukraine; constitutional legislation of Ukraine